Implementation of the Prosperous Home Credit Policy in Minahasa Regency - Kessek, Nonhi Lucky; Tumbel, Goinpeace H.; Siwij, Devie SR (Abdurrauf Science and Society, 2025)
This research uses a qualitative approach with a case study. This approach aims to gain a deep understanding of the meaning and dynamics of the implementation of the Prosperous Home Ownership Credit (KPR Sejahtera) program. Implementation of the Prosperous KPR policy for MBR with non-fixed incomes in Minahasa Regency, The current program is not inclusive. Banking schemes and procedures—which require formal proof of income (pay slips, tax returns, bank statements)—exclude informal sector low-income earners, even those with the ability to make installment payments. This creates an exclusion error, making the program more effective for low-income earners, but failing to reach the core target group of low-income earners. Consequently, the program's achievements risk insignificantly reducing the housing backlog.